Peran Iklim Sekolah terhadap Perilaku Cyberbullying - Waji, Ria Sakinah; Linggi, Alexander Indrakusuma (CV. Ulil Albab Corp, 2025)
The use of digital technology can result in cyberbullying behavior. Cyberbullying behavior is a cruel behavior that disturbs other individuals that is done consciously and repeatedly using technology media. Adolescents as students will spend more time at school. One of the researcher's assumptions is that the influence of the role of school climate has a role in the occurrence of cyberbullying behavior.